Alcune difficoltà traduttive derivanti da una sentenza della Corte Suprema di Cassazione - Loiacono, Rocco (Spunti E Ricerche, 2014)
This paper examines the translational difficulties associated with certain legal terms contained in a judgment of the Corte Suprema di Cassazione, Italy’s highest court, paying particular attention to the translation (into English) of those terms inextricably linked to the Italian legal system. The analysis of the selected terms involves a consideration of the difficulties arising from the divergence between two legal systems, namely, on the one hand, the Italian legal system, which belongs to the civil law family of continental Europe, and on the other, the Australian legal system, which belongs to the English common law tradition. It is proposed that such an analysis offers interesting discussion points with regard to intercultural communication, particularly between different legal cultures.